Subtract.
(2p^2+q)-(p^2+q)
Is the answer
P^2
P^2+2q
P^2-2q
3p^2
1 answer:
Answer:
-p5q2 - p3q5 + 2p3 + 2pq2 + 2q3
____________________________
p3q2
Step-by-step explanation:
2
Simplify ——
q2
Equation at the end of step 1 :
(p+q) 2
(((2•—————)-(q3))+——)-p2
(p3) q2
Step 2 :
p + q
Simplify —————
p3 (p + q) 2
(((2 • ———————) - q3) + ——) - p2
p3 q2
Step 3 : 2 • (p + q) 2
((——————————— - q3) + ——) - p2
p3 q2 q3 q3 • p3
q3 = —— = ———————
1 p3
You might be interested in
Answer:
y=2x+4
Step-by-step explanation:
m=2 because it is perpendicular to (-1/2)
y-12=2(x-4)
y=2x+4
Answer:
2x+3y+32
Step-by-step explanation:
Answer:
the answer is E
Step-by-step explanation:
6 times 4 =24 + area
4+4=8
6+6=12
12+8=20
20=P
For the second one 1 mph equals 1.6 km so i’m pretty sure it would be all of them
Answer:
0.15
Step-by-step explanation: